Salvia miltiorrhiza Bge. (Danshen) for Inflammatory Bowel Disease: Clinical Evidence and Network Pharmacology-Based Strategy for Developing Supplementary Medical Application - Zhang, Siyuan; Luo, Hua; Sun, Shiyi; Zhang, Yating; Ma, Jiaqi; Lin, Yuting; Yang, Lin; Tan, Dechao; Fu, Chaomei; Zhong, Zhangfeng; Wang, Yitao (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) is a non-specific colorectal disease caused by multifaceted triggers. Although conventional treatments are effective in the management of IBD, high cost and frequent side effects limit their applications and have turned sufferers toward alternative and complementary approaches. Salvia miltiorrhiza Bge. (Danshen) is an herbal medicine that reportedly alleviates the symptoms of IBD. A large body of research, including clinical trials in which Danshen-based products or botanical compounds were used, has unmasked its multiple mechanisms of action, but no review has focused on its efficacy as a treatment for IBD. Here, we discussed triggers of IBD, collected relevant clinical trials and analyzed experimental reports, in which bioactive compounds of Danshen attenuated colitis in the management of intestinal integrity, gut microflora, cell death, immune conditions, cytokines, and free radicals. A network pharmacology approach was applied to describe sophisticated mechanisms in a holistic view. This review of evidence will help to better understand the potential benefits of Danshen for IBD treatment and provide insights for the development of innovative applications of Danshen.